Dominant cyanobacterial flora of the Religious ponds at Holy Geeta’s birthplace, Kurukshetra, India - Chandra Bhushan Singh; Biban, Laxmi (Journal of Research in Biology, 2011)
The cyanobacterial biodiversity analysis from different fresh water of holy aquatic bodies was conducted during summer (May-June, 2009) and autumn months (Aug.-Sept., 2009) in the village Jyotisar of Kurukshetra, Haryana, India. Similar studies were performed during the same periods of next year (2010). This place is popularly known as the birthplace of holy ‘Bhagwat Geeta’ (=‘Geeta’s Janmsthal’), which is geographically located at Lat. 29057’53.54”N; Long. 76049’07.56”E. There are mainly two ponds situated there viz. Pond-1 and Pond-2. Both of them were analyzed for their physicochemical and biological properties. Our observations have revealed various noticeable variations recorded in the cyanobacterial flora according to seasonal and environmental variations among the two ancient ponds. Unicellular cyanobacterial strains dominated the Pond-1, where people from all over India take holy dip. Contrary to this, Pond-2 was dominated by mainly filamentous cyanobacteria along with massive growth of higher aquatic plants like Nelumbo. The entire microbial community was dominated chiefly by cyanobacteria and diatoms